Association of childhood obesity with female infertility in adulthood: a 25-year follow-up study - He, Y; Tian, J; Oddy, W; Dwyer, T; Venn, A (Elsevier, 2018)
Objective To evaluate whether childhood obesity is associated with infertility in women's reproductive-aged life. Design Prospective longitudinal study. Setting Not applicable. Intervention(s) None. Patient(s) A total of 1,544 girls, aged 7–15 years in 1985, and who completed questionnaires at follow-up in 2004-2006 and/or 2009-2011. Main Outcome Measure(s) Infertility was defined as having difficulty conceiving (had tried for ≥12 months to become pregnant without succeeding) or having seen a doctor because of trouble becoming pregnant. Result(s) At ages from 7–11 years, girls at both the lower and upper end of the body mass index (BMI) z score had increased risk of infertility. Compared with normal weight girls, those with obesity at ages 7–11 years were more likely in adulthood to report infertility (adjusted relative risk [aRR] = 2.94, 95% confidence interval [CI] 1.48–5.84), difficulty conceiving (aRR = 3.89, 95% CI 1.95–7.77), or having seen a doctor because of trouble becoming pregnant (aRR = 3.65, 95% CI 1.90–7.02) after adjusting for childhood age, follow-up length, highest parental education, and marital status. Conclusion(s) Childhood obesity before 12 years of age appears to increase the risk of female infertility in later life.